High-strength corrosion-resistant steel bar surface epoxy coating and preparation method thereof
By combining modified polyaniline/TiO2 powder with epoxy resin and other components, a high-strength corrosion-resistant epoxy coating is formed, which solves the problem of the existing steel bar surface coating being easily corroded in complex environments, and achieves comprehensive protection of steel bars and Improved durability.
Patent Information
- Application Number
- CN202411452835.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-27
AI Technical Summary
The existing surface coating of steel bars is prone to corrosion in complex environments, with poor toughness, high brittleness, high temperature resistance and poor corrosion resistance, and cannot effectively protect steel bars, resulting in reduced structural load-bearing capacity and safety hazards.
Modified polyaniline/TiO2 high-strength corrosion-resistant epoxy coating is used to prepare modified polyaniline/TiO2 powder by in-situ chemical oxidation synthesis method, and combine it with epoxy resin, zinc phosphate, talc powder and other components to form high temperature resistance , scratch-resistant and corrosion-resistant coating.
It improves corrosion resistance, wear resistance and high temperature resistance of the steel bar surface, extends the service life of the steel bar, reduces costs, and has good environmental friendliness and socio-economic benefits.
Smart Images

Figure CN119192951A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of surface anticorrosion, in particular to a high-strength and corrosion-resistant steel bar surface epoxy coating and a preparation method thereof. Background Art
[0002] Steel bars that have been in service for a long time or exposed to the external environment are susceptible to chloride corrosion or carbonization, which causes the performance of the steel bars to deteriorate and seriously affects the durability and applicability of the structure. For example, bridges, oil platforms or structures treated with deicing salts and concrete beam and slab components located in the splash zone. In recent years, many reinforced concrete components have been affected by steel bar corrosion, resulting in a reduction in structural bearing capacity, causing huge dangers and losses, and also related to a series of major social issues such as environmental protection and energy conservation. In this case, epoxy coatings with high corrosion resistance, aging resistance, impact resistance, and shielding capabilities against acidic gases, oxygen, water molecules, etc. are extremely important. In the past, ordinary epoxy coatings had the disadvantages of poor toughness, high brittleness, easy cracking, not resistant to high temperatures, and poor corrosion resistance, and could not protect steel bars in complex environments. Summary of the invention
[0003] The technical problem to be solved by the present invention is: to overcome the deficiencies in the prior art and provide a high-strength and corrosion-resistant epoxy coating for the surface of steel bars and a preparation method thereof. The modified polyaniline / TiO2 high-strength and corrosion-resistant epoxy coating proposed by the present invention has many advantages such as self-cleaning, scratch resistance, corrosion resistance and wear resistance. Polyaniline has excellent host ability to capture nanoparticles and can be co-doped with some active inorganic nanoparticles to effectively improve its solubility and corrosion resistance. The modified epoxy resin has the characteristics of high temperature resistance, which further provides more comprehensive protection for steel bars. The present invention is low-cost, environmentally friendly, and has good social and economic benefits.
[0004] The technical solution adopted by the present invention to solve its technical problem is:
[0005] A high-strength, corrosion-resistant steel bar surface epoxy coating comprises the following components in parts by weight: 1-5 parts of modified polyaniline / TiO2 powder, 8-10 parts of aluminum tripolyphosphate, 8-10 parts of zinc phosphate, 8-10 parts of talcum powder, 10-15 parts of barium sulfate, 100-200 parts of modified epoxy resin, 50-100 parts of curing agent, 10-20 parts of accelerator and 1-3 parts of leveling agent.
[0006] Furthermore, the preparation method of the modified polyaniline / TiO2 powder is: in-situ polymerizing polyaniline on the surface of nano-TiO2 by in-situ chemical oxidation synthesis to obtain the modified polyaniline / TiO2 powder.
[0007] Furthermore, the modified epoxy resin is an aerogel-pumice composite bisphenol A type epoxy resin.
[0008] Furthermore, the curing agent is polyamide 650, the accelerator is DMP-3, and the leveling agent is polydimethylsiloxane.
[0009] A method for preparing the above-mentioned high-strength and corrosion-resistant steel bar surface epoxy coating specifically comprises the following steps:
[0010] Step S1, preparation of modified polyaniline / TiO2 powder;
[0011] Step S2, preparation of modified epoxy resin, adding powdered pumice and solid aerogel into epoxy resin, stirring evenly to obtain modified epoxy resin;
[0012] Step S3, putting the modified polyaniline / TiO2 powder obtained in step S1 and the modified epoxy resin obtained in step S2 into a container, stirring evenly to obtain a modified mixture; then adding aluminum tripolyphosphate, zinc phosphate, talcum powder, and barium sulfate to the modified mixture in sequence, stirring for 80 minutes, adding a curing agent and an accelerator, stirring for 100 minutes, adding a leveling agent, and continuing to stir for 30 minutes to prepare a finished high-strength and corrosion-resistant steel bar surface epoxy coating.
[0013] Furthermore, the preparation of the modified polyaniline / TiO2 powder in step S1 specifically comprises the following steps:
[0014] Step S11, adding polyaniline to an aqueous solution containing SDBS, then adding nano-TiO2, ethyl hydroxybenzoate and butyl hydroxybenzoate, and stirring with a magnetic stirrer for 80 minutes to obtain a uniform suspension, namely a polyaniline solution;
[0015] Step S12, adding APS to a 10% concentrated hydrochloric acid aqueous solution, stirring with a magnetic stirrer for 40 minutes to obtain an APS solution;
[0016] Step S13, adding the APS solution obtained in step S12 dropwise into the polyaniline solution obtained in step S11, the reaction temperature is 0-5°C, the reaction is continued for 8 hours, and stirring is stopped; then standing for 24 hours, filtered, and washed with deionized water and methanol for multiple times, and then rinsed with a large amount of deionized water until the filtrate is nearly colorless to obtain a solid; vacuum drying at 75°C for 12 hours, drying and grinding into powder, that is, the finished modified polyaniline / TiO2 powder, the modified polyaniline / TiO2 powder has a diameter of 5-10 μm.
[0017] Furthermore, in the step S11, the weight component of polyaniline is 1 to 5 parts, the weight component of the aqueous solution containing SDBS is 50 to 250 parts, and the weight component of nano-TiO2 is 0.5 to 2 parts.
[0018] SDBS is sodium dodecylbenzene sulfonate, a white or light yellow powdery solid with a diameter of 2 to 12 μm. APS is ammonium persulfate, a colorless monoclinic crystal, and a strong oxidant.
[0019] Furthermore, the preparation of the modified epoxy resin in step S2 specifically comprises the following steps:
[0020] Step S21, sieving natural pumice with a particle size of 10 to 18 mm, then rinsing with tap water to remove dust and impurities in the pumice, and then putting the rinsed pumice aggregate into a blast drying oven to dry it to a constant weight;
[0021] Step S22, placing the natural pumice obtained in step S21 in a 0.3-0.5 mol / L HCl solution, controlling the liquid level of the HCl solution to be more than 4 mm above the top surface of the pumice aggregate, stirring for 10-20 minutes, draining the natural pumice, and placing it in a blast drying oven again for drying until it is dried to a constant weight, thereby obtaining the pretreated pumice aggregate, and the performance of the pretreated pumice is more stable;
[0022] Step S23, putting the natural pumice obtained in step S22 into an ultrafine grinding machine, grinding for 20 to 25 minutes, grinding the pumice into fine powder, the diameter of the powdered pumice is 5 to 15 μm;
[0023] Step S24, mixing the powdered pumice obtained in step S23 with the solid aerogel and adding them into epoxy resin, wherein the epoxy resin in this step is bisphenol A epoxy resin, stirring at room temperature for 30 minutes to 40 minutes, and standing for 30 minutes to obtain a finished modified epoxy resin.
[0024] In both steps S21 and S22, the pumice stone is dried at a temperature of 100° C. to 120° C. and for a drying time of 10 to 12 hours.
[0025] Furthermore, in step S24, the weight of the epoxy resin is 100-150 parts, the weight of the powdered pumice is 10-20 parts, and the weight of the solid aerogel is 20-30 parts.
[0026] The beneficial effects of the present invention are as follows: the present invention has a reasonable design, a simple preparation method, and has the following advantages:
[0027] (1) Polyaniline has the advantages of low cost of synthetic raw materials, scratch resistance, corrosion resistance, strong impact resistance and good environmental stability. Polyaniline has excellent host ability to capture nanoparticles and can be doped with some active inorganic nanoparticles to effectively improve its solubility and corrosion resistance.
[0028] (2) Nano-level TiO2 has the characteristics of large specific surface energy, wide band gap, excellent carrier carrying capacity, and low harmful impurity content. Its application in surface engineering is mainly through coating, plating or doping nano-TiO2 on the surface of the base material to achieve the functions of protecting, strengthening, repairing and decorating the base material;
[0029] (3) A modified epoxy resin layer is provided, and the composite of pumice and solid aerogel effectively improves the high temperature resistance of the epoxy resin, and can improve the high temperature resistance of the outer side of the steel bar body, thereby expanding the environmental conditions for the use of the steel bar and increasing the service life of the steel bar;
[0030] (4) The iron phosphate protective film formed on the surface of the substrate by the reaction of zinc phosphate and iron anode is insoluble in water, has high hardness, strong adhesion, and excellent anti-corrosion performance. Zinc phosphate itself is non-toxic and harmless, and has strong anti-rust ability. Aluminum tripolyphosphate has excellent flame retardant properties, which can effectively reduce the combustion performance of materials and improve fire safety. The passivation film formed on the surface of the coating and the substrate can effectively prevent the migration and penetration of corrosive substances, and has a strong inhibitory effect on the corrosion of the steel bar surface. Barium sulfate itself has high temperature resistance and corrosion resistance, and can work together with any other materials to improve the water resistance, wear resistance and impact strength of the coating. Talc powder has the advantages of lubricity, fire resistance, acid resistance, and strong adsorption capacity, and also plays an important role in the preparation of coatings. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 It is a graph of the penetration performance of the high-strength and corrosion-resistant steel bar surface epoxy coating prepared in Examples 1 to 3. DETAILED DESCRIPTION
[0033] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0034] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0035] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] A high-strength, corrosion-resistant steel bar surface epoxy coating comprises the following components in parts by weight: 1-5 parts of modified polyaniline / TiO2 powder, 8-10 parts of aluminum tripolyphosphate, 8-10 parts of zinc phosphate, 8-10 parts of talcum powder, 10-15 parts of barium sulfate, 100-200 parts of modified epoxy resin, 50-100 parts of curing agent, 10-20 parts of accelerator, and 1-3 parts of leveling agent. The curing agent is polyamide 650, the accelerator is DMP-3, and the leveling agent is polydimethylsiloxane.
[0037] A method for preparing the above-mentioned high-strength and corrosion-resistant steel bar surface epoxy coating specifically comprises the following steps:
[0038] Step S1, preparation of modified polyaniline / TiO2 powder;
[0039] Step S11, adding polyaniline to an aqueous solution containing SDBS (sodium dodecylbenzene sulfonate), then adding nano-TiO2, ethyl hydroxybenzoate and butyl hydroxybenzoate, and stirring with a magnetic stirrer for 80 minutes to obtain a uniform suspension, namely a polyaniline solution;
[0040] Step S12, adding APS (ammonium persulfate) to a 10% concentrated hydrochloric acid aqueous solution, stirring with a magnetic stirrer for 40 minutes to obtain an APS solution;
[0041] Step S13, adding the APS solution obtained in step S12 dropwise to the polyaniline solution obtained in step S11, the reaction temperature is 0-5°C, the reaction is continued for 8 hours, and stirring is stopped; then standing for 24 hours, suction filtering, and washing with deionized water and methanol for multiple times, and then rinsed with a large amount of deionized water until the filtrate is nearly colorless to obtain a solid; vacuum drying at 75°C for 12 hours, drying and grinding into powder, that is, the finished modified polyaniline / TiO2 powder;
[0042] Step S2, preparation of modified epoxy resin;
[0043] Step S21, sieving natural pumice with a particle size of 10 to 18 mm, then rinsing with tap water to remove dust and impurities in the pumice, and then putting the rinsed pumice aggregate into a blast drying oven to dry it to a constant weight;
[0044] Step S22, placing the natural pumice obtained in step S21 in a 0.3-0.5 mol / L HCl solution, controlling the liquid level of the HCl solution to be more than 4 mm above the top surface of the pumice aggregate, stirring for 10-20 minutes, draining the natural pumice, and placing it in a blast drying oven again for drying until it is dried to a constant weight, thereby obtaining the pretreated pumice aggregate, and the performance of the pretreated pumice is more stable;
[0045] Step S23, putting the natural pumice obtained in step S22 into an ultrafine grinding machine, grinding for 20 to 25 minutes, and grinding the pumice into fine powder;
[0046] Step S24: Mix the powdered pumice obtained in step S23 with the solid aerogel and add them to the epoxy resin, stir for 30 to 40 minutes at room temperature, and let stand for 30 minutes to obtain a finished modified epoxy resin.
[0047] Step S3, putting the modified polyaniline / TiO2 powder obtained in step S1 and the modified epoxy resin obtained in step S2 into a container, stirring evenly to obtain a modified mixture; then adding aluminum tripolyphosphate, zinc phosphate, talcum powder, and barium sulfate to the modified mixture in sequence, stirring for 80 minutes, adding a curing agent and an accelerator, stirring for 100 minutes, adding a leveling agent, and continuing to stir for 30 minutes to prepare a finished high-strength and corrosion-resistant steel bar surface epoxy coating.
[0048] When the high-strength and corrosion-resistant steel bar surface epoxy coating is used, a layer of the prepared high-strength and corrosion-resistant steel bar surface epoxy coating is applied to the outer layer of the steel bar body, with a coating thickness of between 200 and 300 μm, and the epoxy coating is formed after natural air drying.
[0049] Example 1
[0050] A high-strength, corrosion-resistant steel bar surface epoxy coating (RS3) comprises the following components: 0.288wt% of polyaniline, 0.288wt% of TiO2, 28.818wt% of epoxy resin, 8.646wt% of aluminum tripolyphosphate, 8.646wt% of zinc phosphate, 8.646wt% of talc, 15.85wt% of barium sulfate, 28.818wt% of polyamide component, 2.282wt% of DMP-30 component and 1.113wt% of polydimethylsiloxane component.
[0051] The coating obtained in this embodiment has a grade I adhesion, an impact strength of 50 kg·cm on both sides, excellent flexibility, a pencil hardness of 6H, the best mechanical properties, and the best corrosion resistance. The chloride ion erosion rate is D RCM is 8.19(10 -12 m 2 / s) low frequency impedance modulus is 5.1.
[0052] Example 2
[0053] A high-strength, corrosion-resistant steel bar surface epoxy coating (RS2) comprises the following components: 0.412wt% of polyaniline, 0.412wt% of TiO2, 41.2wt% of epoxy resin, 5.646wt% of aluminum tripolyphosphate, 5.646wt% of zinc phosphate, 5.646wt% of talc, 10.85wt% of barium sulfate, 26.112wt% of polyamide component, 2.282wt% of DMP-30 component and 1.794wt% of polydimethylsiloxane component.
[0054] The coating obtained in this example has a grade I adhesion, an impact strength of 50 kg·cm on the front side and 40 kg·cm on the back side, excellent flexibility, a pencil hardness of 6H, excellent mechanical properties, excellent corrosion resistance, and a chloride ion erosion rate of D RCM is 8.62(10 -12 m 2 / s), the low frequency impedance modulus is 4.814.
[0055] Example 3
[0056] A high-strength, corrosion-resistant steel bar surface epoxy coating (RS1) comprises the following components: 0.576wt% of polyaniline, 0.576wt% of TiO2, 57.6wt% of epoxy resin, 4.434wt% of aluminum tripolyphosphate, 4.434wt% of zinc phosphate, 4.434wt% of talc, 7.622wt% of barium sulfate, 22.632wt% of polyamide component, 1.35wt% of DMP-30 component and 0.776wt% of polydimethylsiloxane component.
[0057] The coating obtained in this example has a grade I adhesion, an impact strength of 40 kg·cm on the front side and 20 kg·cm on the back side, excellent flexibility, a pencil hardness of 5H, good mechanical properties, good corrosion resistance, and a chloride ion erosion rate of D RCM is 11.06(10 -12 m 2 / s), the low frequency impedance modulus is 4.42.
[0058] Example 4
[0059] A high-strength, corrosion-resistant steel bar surface epoxy coating (RS4) comprises the following components: 0.306wt% of polyaniline, 0.306wt% of TiO2, 59.3wt% of epoxy resin, 3.622wt% of aluminum tripolyphosphate, 3.622wt% of zinc phosphate, 3.622wt% of talc, 7.841wt% of barium sulfate, 19.412wt% of polyamide component, 1.22wt% of DMP-30 component and 0.749wt% of polydimethylsiloxane component.
[0060] The coating obtained in this example has a grade I adhesion, an impact strength of 50 kg·cm on the front side and 10 kg·cm on the back side, excellent flexibility, a pencil hardness of 6H, good mechanical properties, and a chloride ion erosion rate of D RCM is 11.32(10 -12 m 2 / s), and the low-frequency impedance modulus is 4.33.
[0061] Example 5
[0062] A high-strength, corrosion-resistant steel bar surface epoxy coating (RS5) comprises the following components: 0.46wt% polyaniline, 0.46wt% TiO2, 56.37wt% epoxy resin, 4.166wt% aluminum tripolyphosphate, 4.166wt% zinc phosphate, 4.166wt% talc, 8.13wt% barium sulfate, 20.66wt% polyamide component, 1.02wt% DMP-30 component and 0.402wt% polydimethylsiloxane component.
[0063] The coating obtained in this example has a grade I adhesion, an impact strength of 50 kg·cm on the front side and 20 kg·cm on the back side, excellent flexibility, a pencil hardness of 6H, good mechanical properties, and a chloride ion erosion rate of D RCM is 11.29(10 -12 m 2 / s), and the low-frequency impedance modulus is 4.51.
[0064] Example 6
[0065] A high-strength, corrosion-resistant steel bar surface epoxy coating (RS6) comprises the following components: 0.51wt% polyaniline, 0.51wt% TiO2, 53.44wt% epoxy resin, 5.72wt% aluminum tripolyphosphate, 5.72wt% zinc phosphate, 5.72wt% talc, 7.3wt% barium sulfate, 20.01wt% polyamide component, 0.7wt% DMP-30 component, and 0.57wt% polydimethylsiloxane component.
[0066] The coating obtained in this example has a grade I adhesion, an impact strength of 50 kg·cm on the front side and 30 kg·cm on the back side, excellent flexibility, a pencil hardness of 5H, good mechanical properties, and a chloride ion erosion rate of D RCM is 13.2(10 -12 m 2 / s), and the low-frequency impedance modulus is 4.40.
[0067] Example 7
[0068] A high-strength, corrosion-resistant steel bar surface epoxy coating (RS7) comprises the following components: 0.6wt% polyaniline, 0.6wt% TiO2, 60.33wt% epoxy resin, 6.111wt% aluminum tripolyphosphate, 6.111wt% zinc phosphate, 6.111wt% talc, 5.22wt% barium sulfate, 13.432wt% polyamide component, 0.92wt% DMP-30 component, and 0.613wt% polydimethylsiloxane component.
[0069] The coating obtained in this example has a grade I adhesion, an impact strength of 50 kg·cm on the front side and 4 kg·cm on the back side, excellent flexibility, a pencil hardness of 6H, good mechanical properties, and a chloride ion erosion rate of D RCM is 14.41(10 -12 m 2 / s), and the low-frequency impedance modulus is 4.39.
[0070] Example 8
[0071] A high-strength, corrosion-resistant steel bar surface epoxy coating (RS8) comprises the following components: 0.72wt% of polyaniline, 0.72wt% of TiO2, 60.18wt% of epoxy resin, 6.31wt% of aluminum tripolyphosphate, 6.31wt% of zinc phosphate, 6.31wt% of talc, 4.75wt% of barium sulfate, 12.455wt% of polyamide component, 1.406wt% of DMP-30 component and 0.839wt% of polydimethylsiloxane component.
[0072] The coating obtained in this example has a grade I adhesion, an impact strength of 50 kg·cm on the front side and 50 kg·cm on the back side, excellent flexibility, a pencil hardness of 6H, good mechanical properties, and a chloride ion erosion rate of D RCM is 14.14(10 -12 m 2 / s), and the low-frequency impedance modulus is 4.33.
[0073] Example 9
[0074] A high-strength, corrosion-resistant steel bar surface epoxy coating (RS9) comprises the following components: 0.8wt% polyaniline, 0.8wt% TiO2, 60.6wt% epoxy resin, 6.12wt% aluminum tripolyphosphate, 6.12wt% zinc phosphate, 6.12wt% talc, 4.63wt% barium sulfate, 12.7wt% polyamide component, 1.44wt% DMP-30 component and 0.67wt% polydimethylsiloxane component.
[0075] The coating obtained in this example has a grade I adhesion, an impact strength of 40 kg·cm on the front side and 50 kg·cm on the back side, excellent flexibility, a pencil hardness of 6H, good mechanical properties, and a chloride ion erosion rate of D RCM is 15.17(10 -12 m 2 / s), and the low-frequency impedance modulus is 4.31.
[0076] Comparative Example 1
[0077] The invention discloses an epoxy coating (DM1) for the surface of steel bars, comprising the following components: 0.312 wt% of polyaniline, 31.2 wt% of epoxy resin, 6.64 wt% of ammonium ferric phosphate, 6.64 wt% of zinc phosphate, 6.64 wt% of talc, 8.412 wt% of nano-barium phosphate, 32.9 wt% of polyamide component, 5.16 wt% of DMP-30 component and 2.096 wt% of polydimethylsiloxane component.
[0078] The coating obtained in this comparative example has a grade II adhesion, an impact strength of 40 kg·cm on the front side and 20 kg·cm on the back side, good flexibility, a pencil hardness of 5H, good mechanical properties, poor corrosion resistance, and a chloride ion permeability resistance of up to 17.62 (10 -12 m 2 / s), and the low-frequency impedance modulus is 3.943.
[0079] From Examples 1 to 9 and Comparative Example 1, it can be seen that the content of polyaniline and TiO2 seriously affects the corrosion resistance of the coating. The polyaniline / TiO2 nanoparticles contain all the typical absorption peaks in polyaniline. The synthesized polyaniline / TiO2 particles are nanometer-level and the particles are evenly dispersed. The crystallinity of the synthesized polyaniline is not high, and the strong interaction between TiO2 and polyaniline limits the crystallization of polyaniline. This limiting effect becomes more obvious as the content of polyaniline and TiO2 increases. The limitation of polyaniline crystallization significantly affects its corrosion resistance. The present invention selects the preferred coating formula RS3 and verifies it through experiments. The components of Comparative Example 1 do not include modified polyaniline / TiO2 powder, so the performance parameters are not as good as those of Examples 1 to 9.
[0080] The high-strength and corrosion-resistant steel bar surface epoxy coatings prepared in Examples 1 to 3 were coated on the outer layer of the steel bar body, respectively, to prepare samples RS1, RS2 and RS3, and the permeability test was carried out with ordinary steel bars S1, S2 and S3. The experimental process is: the epoxy-coated steel bars and ordinary steel bars are immersed in a 5% NaCl solution at room temperature for 120 hours. The experimental results are shown in FIG. Figure 1 As shown. Figure 1 It can be seen that the corrosion resistance of the steel bars coated with the high-strength and corrosion-resistant steel bar surface epoxy coating prepared in Examples 1 to 3 is significantly better than that of ordinary steel bars.
[0081] The high-strength and corrosion-resistant steel bar surface epoxy coatings prepared in Examples 4 to 9 were respectively coated on the outer layer of the steel bar body, and mechanical property tests were performed. The test results are shown in Table 1.
[0082] Table 1 Mechanical properties test results of Examples 4 to 9
[0083] Test piece number hardness Impact strength (kg cm) Flexibility Example 4 (RS4) 6H 50 positive and 10 negative Micro cracks, no peeling Example 5 (RS5) 6H 50 positive and 20 negative Micro cracks, no peeling Example 6 (RS6) 5H 50 positive and 30 negative Micro cracks, no peeling Example 7 (RS7) 6H 50 positive and 40 negative No cracks, no peeling Example 8 (RS8) 6H 50 positive and 50 negative No cracks, no peeling Example 9 (RS10) 6H Positive 40 negative 50 Micro cracks, no peeling
[0084] It can be seen from Table 1 that the high-strength and corrosion-resistant steel bar surface epoxy coatings prepared in Examples 4 to 9 have high strength and impact resistance, and can effectively protect steel bars in complex environments.
[0085] In summary, the present invention has the following advantages:
[0086] (1) Polyaniline has the advantages of low cost of synthetic raw materials, scratch resistance, corrosion resistance, strong impact resistance and good environmental stability. Polyaniline has excellent host ability to capture nanoparticles and can be doped with some active inorganic nanoparticles to effectively improve its solubility and corrosion resistance.
[0087] (2) Nano-level TiO2 has the characteristics of large specific surface energy, wide band gap, excellent carrier carrying capacity, and low harmful impurity content. Its application in surface engineering is mainly through coating, plating or doping nano-TiO2 on the surface of the base material to achieve the functions of protecting, strengthening, repairing and decorating the base material;
[0088] (3) A modified epoxy resin layer is provided, and the composite of pumice and solid aerogel effectively improves the high temperature resistance of the epoxy resin, and can improve the high temperature resistance of the outer side of the steel bar body, thereby expanding the environmental conditions for the use of the steel bar and increasing the service life of the steel bar;
[0089] (4) The iron phosphate protective film formed on the surface of the substrate by the reaction of zinc phosphate and iron anode is insoluble in water, has high hardness, strong adhesion, and excellent anti-corrosion performance. Zinc phosphate itself is non-toxic and harmless, and has strong anti-rust ability. Aluminum tripolyphosphate has excellent flame retardant properties, which can effectively reduce the combustion performance of materials and improve fire safety. The passivation film formed on the surface of the coating and the substrate can effectively prevent the migration and penetration of corrosive substances, and has a strong inhibitory effect on the corrosion of the steel bar surface. Barium sulfate itself has high temperature resistance and corrosion resistance, and can work together with any other materials to improve the water resistance, wear resistance and impact strength of the coating. Talc powder has the advantages of lubricity, fire resistance, acid resistance, and strong adsorption capacity, and also plays an important role in the preparation of coatings.
[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-strength, corrosion-resistant epoxy coating for steel bar surface, characterized in that: The invention comprises the following components in parts by weight: 1-5 parts of modified polyaniline / TiO2 powder, 8-10 parts of aluminum tripolyphosphate, 8-10 parts of zinc phosphate, 8-10 parts of talcum powder, 10-15 parts of barium sulfate, 100-200 parts of modified epoxy resin, 50-100 parts of curing agent, 10-20 parts of accelerator and 1-3 parts of leveling agent.
2. The high-strength, corrosion-resistant epoxy coating for steel bar surface according to claim 1, characterized in that: The preparation method of the modified polyaniline / TiO2 powder is as follows: in-situ polymerization of polyaniline on the surface of nano-TiO2 is carried out by an in-situ chemical oxidation synthesis method to obtain the modified polyaniline / TiO2 powder.
3. The high-strength, corrosion-resistant epoxy coating for steel bar surface according to claim 1, characterized in that: The modified epoxy resin is an aerogel-pumice compound bisphenol A type epoxy resin.
4. The high-strength, corrosion-resistant epoxy coating for steel bar surface according to claim 1, characterized in that: The curing agent is polyamide 650.
5. A method for preparing the high-strength and corrosion-resistant steel bar surface epoxy coating according to any one of claims 1 to 4, characterized in that: The specific steps include: Step S1, preparation of modified polyaniline / TiO2 powder; Step S2, preparation of modified epoxy resin, adding powdered pumice and solid aerogel into epoxy resin, stirring evenly to obtain modified epoxy resin; Step S3, putting the modified polyaniline / TiO2 powder obtained in step S1 and the modified epoxy resin obtained in step S2 into a container, stirring evenly to obtain a modified mixture; then adding aluminum tripolyphosphate, zinc phosphate, talcum powder, and barium sulfate to the modified mixture in sequence, stirring for 80 minutes, adding a curing agent and an accelerator, stirring for 100 minutes, adding a leveling agent, and continuing to stir for 30 minutes to prepare a finished high-strength and corrosion-resistant steel bar surface epoxy coating.
6. The method for preparing a high-strength and corrosion-resistant steel bar surface epoxy coating according to claim 5, characterized in that: The preparation of modified polyaniline / TiO2 powder in step S1 specifically comprises the following steps: Step S11, adding polyaniline to an aqueous solution containing SDBS, then adding nano-TiO2, ethyl hydroxybenzoate and butyl hydroxybenzoate, and stirring with a magnetic stirrer for 80 minutes to obtain a uniform suspension, namely a polyaniline solution; Step S12, adding APS to a 10% concentrated hydrochloric acid aqueous solution, stirring with a magnetic stirrer for 40 minutes to obtain an APS solution; Step S13, adding the APS solution obtained in step S12 dropwise into the polyaniline solution obtained in step S11, the reaction temperature is 0-5°C, the reaction is continued for 8 hours, and stirring is stopped; then standing for 24 hours, filtered, and washed with deionized water and methanol for multiple times, and then rinsed with a large amount of deionized water until the filtrate is nearly colorless to obtain a solid; vacuum drying at 75°C for 12 hours, drying and grinding into powder to obtain the finished modified polyaniline / TiO2 powder.
7. The method for preparing a high-strength and corrosion-resistant steel bar surface epoxy coating according to claim 6, characterized in that: In the step S11, the weight component of polyaniline is 1 to 5 parts, the weight component of the aqueous solution containing SDBS is 50 to 250 parts, and the weight component of nano-TiO2 is 0.5 to 2 parts.
8. The method for preparing a high-strength and corrosion-resistant steel bar surface epoxy coating according to claim 5, characterized in that: The preparation of the modified epoxy resin in step S2 specifically comprises the following steps: Step S21, sieving natural pumice with a particle size of 10 to 18 mm, then rinsing with tap water to remove dust and impurities in the pumice, and then putting the rinsed pumice aggregate into a blast drying oven to dry it to a constant weight; Step S22, placing the natural pumice obtained in step S21 in a 0.3-0.5 mol / L HCl solution, controlling the liquid level of the HCl solution to be more than 4 mm above the top surface of the pumice aggregate, stirring for 10-20 minutes, draining the natural pumice, and placing it in a blast drying oven again for drying until it is dried to a constant weight, thereby obtaining the pretreated pumice aggregate, and the performance of the pretreated pumice is more stable; Step S23, putting the natural pumice obtained in step S22 into an ultrafine grinding machine, grinding for 20 to 25 minutes, and grinding the pumice into fine powder; Step S24, mixing the powdered pumice obtained in step S23 with the solid aerogel and adding them into the epoxy resin, stirring at room temperature for 30 minutes to 40 minutes, and standing for 30 minutes to obtain a finished modified epoxy resin.
9. The method for preparing a high-strength and corrosion-resistant steel bar surface epoxy coating according to claim 8, characterized in that: In the step S24, the weight of the epoxy resin is 100-150 parts, the weight of the powdered pumice is 10-20 parts, and the weight of the solid aerogel is 20-30 parts.
Citation Information
Patent Citations
Protective fence with surface coated with organic epoxy coating and making method
CN105925172A
Composite high-temperature-resistant and anti-shearing FRP rib and preparation method thereof
CN118650911A
Polyaniline coated nano TiO2 and poly aniline coated TiO2 whisker and their preparing method
CN1821315A
Cited By
Coating for concrete reinforcement and preparation method thereof
CN122404613A